Innovation and business performance in Australia: Role of entrepreneurship and intrapreneurship in a crisis - Abeysekera, Indra (Frontiers in Psychology, 2023)
This descriptive study aimed to examine entrepreneurship’s and intrapreneurship's roles in translating innovation intention into performance by examining Australian businesses. The primary aim was to investigate whether innovation-active businesses outperformed non-innovation-active businesses. It used the summary data published by the Australian Bureau of Statistics about business innovations during the 2020-2021 financial year. The study included intrapreneurship and entrepreneurship as mediator constructs to hypothesised research questions. The study descriptively analysed data that compared performance increases from the 2019-2020 to 2020-2021 financial year of the Covid-19 crisis period. It found that innovation-active businesses outperformed non-innovation-active businesses. The performance increased with the size of the business, with large businesses performing best, followed by medium-sized and small businesses. There was no distinctive difference between those with innovation-active and non-innovation-active status for businesses that maintained the same or decreased performance. The Theory of Planned Behaviour provided the theoretical framework for the study. The study also found businesses post-crisis have broadened their performance outlook towards a triple bottom line way of thinking, contributing to economic, social, and environmental performance. Considering the findings, the study suggests some policy changes to help businesses thrive after the Covid-19 period.